2021
DOI: 10.1016/j.rbmo.2021.01.023
|View full text |Cite
|
Sign up to set email alerts
|

Individualized follitropin delta dosing reduces OHSS risk in Japanese IVF/ICSI patients: a randomized controlled trial

Abstract: Please cite this article as: Osamu Ishihara , Joan-Carles Arce , for the Japanese Follitropin Delta Phase 3 Trial (STORK) Group, Personalised modulation of ovarian response reduces OHSS risk: a randomised, controlled, assessor-blind trial comparing individualised follitropin delta versus conventional rFSH dosing in Japanese IVF/ICSI patients,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
81
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 42 publications
(85 citation statements)
references
References 29 publications
4
81
0
Order By: Relevance
“…The current study is the first RCT investigating the use of individualised gonadotropin dosing in Asian IVF/ICSI patients and adequately powered for pregnancy outcomes. It demonstrated the efficacy and safety of follitropin delta in Asian women undergoing ovarian stimulation, and clinically validated the appropriateness of the individualised follitropin delta fixed-dose regimen in a wider Asian population beyond the confirmation already reported for Japanese patients ( Ishihara and Arce, 2021 ). In addition to establishing non-inferiority of individualised follitropin delta to conventional follitropin alfa with respect to the primary endpoint of ongoing pregnancy rate, the present trial furthermore showed that the individualised follitropin delta dosing approach has the potential for efficacy benefits beyond the recognised advantages in safety and treatment efficiency ( Nyboe Andersen and Nelson et al , 2017 ; Bosch et al , 2019 ; Ishihara and Arce, 2021 ).…”
Section: Discussionmentioning
confidence: 52%
See 3 more Smart Citations
“…The current study is the first RCT investigating the use of individualised gonadotropin dosing in Asian IVF/ICSI patients and adequately powered for pregnancy outcomes. It demonstrated the efficacy and safety of follitropin delta in Asian women undergoing ovarian stimulation, and clinically validated the appropriateness of the individualised follitropin delta fixed-dose regimen in a wider Asian population beyond the confirmation already reported for Japanese patients ( Ishihara and Arce, 2021 ). In addition to establishing non-inferiority of individualised follitropin delta to conventional follitropin alfa with respect to the primary endpoint of ongoing pregnancy rate, the present trial furthermore showed that the individualised follitropin delta dosing approach has the potential for efficacy benefits beyond the recognised advantages in safety and treatment efficiency ( Nyboe Andersen and Nelson et al , 2017 ; Bosch et al , 2019 ; Ishihara and Arce, 2021 ).…”
Section: Discussionmentioning
confidence: 52%
“…It demonstrated the efficacy and safety of follitropin delta in Asian women undergoing ovarian stimulation, and clinically validated the appropriateness of the individualised follitropin delta fixed-dose regimen in a wider Asian population beyond the confirmation already reported for Japanese patients ( Ishihara and Arce, 2021 ). In addition to establishing non-inferiority of individualised follitropin delta to conventional follitropin alfa with respect to the primary endpoint of ongoing pregnancy rate, the present trial furthermore showed that the individualised follitropin delta dosing approach has the potential for efficacy benefits beyond the recognised advantages in safety and treatment efficiency ( Nyboe Andersen and Nelson et al , 2017 ; Bosch et al , 2019 ; Ishihara and Arce, 2021 ). Women using the individualised follitropin delta dosing regimen achieved significantly higher live birth rates compared to the women treated with a conventional dosing regimen; a trend observed already for the earlier pregnancy parameter of positive βhCG rate.…”
Section: Discussionmentioning
confidence: 52%
See 2 more Smart Citations
“…Comprehensive clinical trials have been performed in in vitro fertilization (IVF)/intracytoplasmic sperm injection (ICSI) patients undergoing ovarian stimulation to document the efficacy and safety of follitropin delta versus CHO-derived recombinant FSH preparations [8][9][10][11][12][13]. The trials have mainly focused on fresh cycles and have provided reassuring information on follitropin delta with respect to the clinical performance of fresh blastocysts leading to pregnancy and live birth as well as the safety of the patients.…”
Section: Introductionmentioning
confidence: 99%